PERANCANGAN FASILITAS KERJA YANG ERGONOMIS PADA AKTIVITAS PENGEMASAN KERUPUK DI UKM KERUPUK LATANSA - Endrian, Bayu; Zetli, Sri (Computer Science and Industrial Engineering, 2025)
Small and Medium Enterprises (SMEs) in Indonesia continue to experience rapid growth, including Kerupuk Latansa SME in Batam City. However, the packaging activities at this SME are still performed using non-ergonomic work facilities, causing physical complaints among workers. This study aims to identify the level of Musculoskeletal Disorders (MSDs) experienced by workers and to design ergonomic work facilities to improve posture and enhance work comfort. The methods used in this research include posture analysis using RULA (Rapid Upper Limb Assessment) and identification of physical complaints through the Nordic Body Map (NBM) questionnaire. Workers' anthropometric data were used as the basis for designing the work facilities. The results of the study revealed that the most common MSD complaints occurred in the neck, shoulders, back, upper arms, waist, knees, and calves, with a high-risk category. The total percentage of MSD complaints was 64% for Worker 1, 43% for Worker 2, 63% for Worker 3, and 64% for Worker 4. As a solution, an ergonomic worktable was designed with specifications of 90.6 cm in height, 250 cm in length, a partition height of 20 cm, and a table tilt angle of 100°, adjusted according to workers' anthropometric data.